2019
DOI: 10.3906/elk-1808-26
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-shaped efficient delay and data gathering routing protocol for underwater wireless sensor networks

Abstract: High end-to-end delay is a major challenge in autonomous underwater vehicle (AUV)-aided routing protocols for underwater monitoring applications. In this paper, a new routing protocol called atomic-shaped efficient delay and data gathering (ASEDG) has been introduced for underwater wireless sensor networks. The ASEDG is divided into two phases; in the first phase, the atomic-shaped trajectory model with horizontal and vertical ellipticals was designed for the movement of the AUV. In the second phase, two types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Furthermore, in our previous work like [41][42][43][44][45] in which, we performed simulation under different traffic agents such that TCP and UDP. In addition, link failure detection between two nodes, subnet based approach and some relevant article to support our words, for this, see [46][47][48][49][50].…”
Section: F Layer Angle Based Flooding (L2-abf)mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, in our previous work like [41][42][43][44][45] in which, we performed simulation under different traffic agents such that TCP and UDP. In addition, link failure detection between two nodes, subnet based approach and some relevant article to support our words, for this, see [46][47][48][49][50].…”
Section: F Layer Angle Based Flooding (L2-abf)mentioning
confidence: 99%
“…A lot of location-based routing protocols have been proposed. But in the water, it is quite difficult to get location information due to the unavailability of GPS [43] [44]. Instead of using location information, DBR uses the depth of sensors for forwarding packets.…”
Section: Comparison With Dbrmentioning
confidence: 99%
“…In addition, the atomic shape-based data gathering routing protocol is already added to our contribution in the literature [ 9 , 10 ] for efficient delay and data gathering purposes. For this purpose, Autonomous Underwater Vehicles (AUV) are deployed along with member and gateway nodes [ 11 ]. Underwater AUVs are responsible for transferring the data to the derived destination without using internode adjustment; however, the long, unnecessary propagation delay occurs [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Extensive simulations were conducted, where the state-of-the-art routing protocols like AVH-AHH-VBF [ 9 ], ASEDG [ 11 ], AEDG [ 13 ], EBER 2 [ 14 ], and WDFAD-DBR [ 15 ] were compared. It was demonstrated that the ROBINA outperforms affordable EC, minimum E2E delay, and high PDR.…”
Section: Introductionmentioning
confidence: 99%
“…In [1], a model-predictive controller MPC is proposed to control depth signals using quadratic programming, and in [2] the researcher discusses a model-free reinforcement learning algorithm for the AUV. Additionally, in [3] applied a neural network for a consensus multiple tracking AUV problems, in [4] a routing protocol is proposed to solve the end-to-end delay in AUV System, and finally on [5] discussed the adaptive AUV system design. In this research work,  ISSN: 1693-6930 an nonlinear fractional order proportional integral derivative (NL-FOPID) AUV is intended to solve the unknown disturbances' problems that affect system response and compared to the relative PID controller.…”
Section: Introductionmentioning
confidence: 99%